Myomodulation as a treatment in correction of gingival smile: a viable alternative? (Research, Society and Development, 2022)
Introduction: The search for an aesthetic smile makes more people look for dental offices, since dentistry has several mechanisms to provide a harmonious smile for the patient. One of the therapeutic possibilities for correcting gummy smile is through the use of hyaluronic acid (myomodulation), a technique with satisfactory results for the patient and less invasive, when compared to other treatment modalities. Objective: To report a clinical case of gummy smile, in which the treatment option was myomodulation. Case report: Female patient presented as main complaint the gingival exposure of the smile. An evaluation was performed through clinical and photographic examination, and the levator labii superioris muscle was chosen as a target to control its activity and restrict muscle movement. The application of 0.4ml of hyaluronic acid will be carried out on each side and the due follow-up of the clinical case. Conclusion: The realization of a careful diagnosis is extremely important to evaluate the primary cause of gingival smile, so that the patient is promoted the best possible treatment plan.